PENGGUNAAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN MINAT DAN PEMAHAMAN KONSEP IPA SISWA KELAS IV MI DARUSALAM BENGKULU TENGAH - Mei Sri Pratiwi; Fitriyah; Komplit Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to describe the use of animated video media in increasing interest in learning and understanding of Natural Science (IPA) concepts in grade IV students of MI Darusalam Bengkulu Tengah. The study used a descriptive qualitative approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results of the study showed that the use of animated video media significantly increased students' interest in learning and made it easier to understand science concepts that were previously considered difficult. Animated videos act as visual-auditory stimuli that help clarify material and increase student interaction during the learning process. Thus, this media is recommended to be integrated into science learning at the elementary school level.